IMPROVING NARRATIVE WRITING ABILITY BY USING PICTURES - Asfah, Indrawaty (Universitas Negeri Makassar, 2019)
This study aims to improve the ability to write narratives for SMP or Junior High School students. The subjects of this study were 32 students class VII A SMP Bayangkara Makassar. Learning is carried out using pictures as the media. Data collection uses observation, assessment rubrics, interviews, journals, and photo for documentation. The results of the study show that the use of radiant color, attractive, simple, easy to understand pictures as a media and delivered in the best presentation, can improve students’ narrative writing